Oncoplastic breast surgery: the role of negative pressure wound therapy. (2nd December 2020) - Iqbal, Fahad M; Reid, Jeremy P; Vidya, Raghavan
Abstract : Wound-related problems following breast surgery are common. Delayed wound healing can lead to poor cosmesis and, among breast cancer patients, can result in delays in receiving adjuvant treatment. The aim of our review was to look at the literature in relation to the role of negative pressure wound therapy in oncoplastic breast surgery, as at the time of writing, there is no consensus on the use of prophylactic negative pressure dressings in closed wounds following breast surgery.